Bioassay-guided isolation of two antiproliferative metabolites from Pterocarpus indicus Willd. against TGF-β-induced prostate stromal cells (WPMY-1) proliferation via PI3K/AKT signaling pathway - Nwe, San Yoon; Uttarawichien, Tamonwan; Boonsom, Teerawat; Thongphichai, Wisuwat; Dasuni Wasana, Peththa Wadu; Sritularak, Boonchoo; Payuhakrit, Witchuda; Sukrong, Suchada; Towiwat, Pasarapa (Frontiers in Pharmacology, 2024)
Benign prostatic hyperplasia (BPH) is the enlargement of the prostate gland, primarily occurring in aging men, in which transforming growth factor-beta (TGF-β) plays a critical role in prostate cell hyperproliferation and leads to uncomfortable urinary symptoms in BPH patients. Pterocarpus indicus Willd. is well known for its ethnopharmacological applications for treating ailments such as diuresis and bladder stones. This study aimed to examine the effect of P. indicus extract (PI extract) on TGF-β-induced WPMY-1 cell proliferation, followed by bioassay-guided fractionation to isolate the active metabolites. Angolensin (Ang) and maackiain (Mac) were isolated from bioassay-guided fractionation. Network analysis was performed to investigate the potential mechanisms. Furthermore, network analysis of the Ang-Mac combination in BPH highlighted the potential top ten pathways, including PI3K/AKT signaling pathway. Accordingly, subsequent investigation focused on evaluating the effect of PI extract, Ang, Mac, and Ang-Mac combination on the expression of PCNA, p53, and PI3K/AKT protein localization and expression. Results revealed inhibition of cell proliferation in TGF-β-induced WPMY-1 cells, correlating with downregulated PCNA expression. While PI extract and Mac induced apoptosis via p53 upregulation, Ang and Ang-Mac combination did not significantly affect apoptosis through the p53 pathway. Additionally, both metabolites exhibited potent inhibition of p-PI3K and p-AKT protein localization and expression in the nucleus of TGF-β-induced WPMY-1 cells. This study suggests that PI extract, Ang, and Mac are promising compounds for treating BPH, as evidenced by in silico and in vitro studies. Additionally, Ang and Mac could be used to standardize PI extract in future investigations.